Strategi Pendidik Dalam Meningkatkan Kemampuan Membaca di Kelas Tinggi - Adha Zam Zam Hariro; Armilah Armilah; Fadya Safitri Rahman; Irlyanova Sabina; Nita Afriani Siregar (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2023)
The purpose of this research is to find out which strategy done by Educators in Improving Reading Ability Students In High Class and to know Factors Supporting and Inhibiting Strategies in educators Improving Students' Reading Ability in high grades. The type of this research is qualitative research field. The data collection technique is by technique interview, observation, and documentation. Deep subject this study are teachers and students. Based on the results research it can be concluded that the Educator Strategy In Improving Students' Reading Ability In High Grades has been carried out by the teacher in grade 4, namely by doing direct learning strategy, not learning strategy direct, interactive learning strategies, learning strategies through experience, and independent learning strategies. Factor which affects the ability to improve reading students namely supporting factors that include, facilities and infrastructure, effective teaching materials/materials, and adequate facilities, while the inhibiting factors are environmental factors, lack of student interest in reading, intellectual factors (intelligence) and factors from parents.